2019
DOI: 10.1098/rspa.2018.0605
|View full text |Cite|
|
Sign up to set email alerts
|

The unified transform for mixed boundary condition problems in unbounded domains

Abstract: This paper implements the unified transform to problems in unbounded domains with solutions having corner singularities. Consequently, a wide variety of mixed boundary condition problems can be solved without the need for the Wiener–Hopf technique. Such problems arise frequently in acoustic scattering or in the calculation of electric fields in geometries involving finite and/or multiple plates. The new approach constructs a global relation that relates known boundary data, such as the scattered normal velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…As a simple demonstration of the method, we now briey consider the case of three rigid plates with γ 1 = [−4, 1], γ 2 = [1.1, 2] and γ 3 = [3,5]. We chose q I = e −ik 0 x cos θ−ik 0 y sin θ for k 0 = 20 and θ = π/4.…”
Section: Example With 3 Rigid Platesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a simple demonstration of the method, we now briey consider the case of three rigid plates with γ 1 = [−4, 1], γ 2 = [1.1, 2] and γ 3 = [3,5]. We chose q I = e −ik 0 x cos θ−ik 0 y sin θ for k 0 = 20 and θ = π/4.…”
Section: Example With 3 Rigid Platesmentioning
confidence: 99%
“…Inspired by the previous numerical method for elastic plates, [3], this paper presents an alternative spectral boundary-based method for obtaining the scattered eld due to the interaction of acoustic sources with nite elastic plates, adapted from a similar approach used for rigid plates [5]. This approach, centred around taking the unied transform [11] (also known as the Fokas transform) of the governing equations both for the structural and acoustic elds, allows us to combine these equations in spectral space and avoids having to calculate singular integrals as is often problematic for BEM codes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our goal in this article is to extend this analysis to linked boundary conditions. A key tool in our analysis is the unified transform (also known as the Fokas method), a novel transform for analyzing boundary value problems for linear (and integrable nonlinear) partial differential equations (PDEs) 7–19 . An excellent pedagogical review of this method can be found in the paper of Deconinck et al 20 …”
Section: Introductionmentioning
confidence: 99%
“…The method is illustrated first for the simple problem of acoustic scattering by a finite rigid flat plate 7 , for which a fully analytic solution is known in terms of Mathieu functions. 8 Results are then given for acoustic scattering by a finite elastic plate, and quadrupole scattering by rigid plates with finite elastic extensions.…”
Section: Introductionmentioning
confidence: 99%